Cox-LASSO Analysis for Hospital Mortality in Patients With Sepsis Received Continuous Renal Replacement Therapy: A MIMIC-III Database Study - Wang, Chunxia; Zheng, Jianli; Wang, Jinxia; Zou, Lin; Zhang, Yucai (Frontiers in Medicine, 2022)
Background: Sepsis remains the leading cause of mortality in-hospital in the intensive care unit (ICU). Continuous renal replacement therapy (CRRT) is recommended as an adjuvant therapy for hemodynamics management in patients with sepsis. The aim of this study was to develop adaptive LASSO for the Cox regression model to predict the hospital mortality in patients with Sepsis-3.0 undergoing CRRT using MIMIC-III v1.4. Methods: Patients who met Sepsis-3.0 definition were identified using the MIMIC-III v1.4. Among them, patients received CRRT during ICU hospitalization were included in this study. According to the survival status, patients were split into death or survival group. Adaptive LASSO for the Cox regression model were constructed by STATA software. At last, nomogram and Kaplan–Meier curves were drawn to validate the model. Results: A total of 181 patients met Sepsis 3.0 criteria received CRRT were included in the study, in which, 31 patients were death and 150 survivals during hospitalization, respectively. The overall in-hospital mortality was 17.1%. According to the results of multivariate Cox-LASSO regression analysis, use of vasopressor, INR >1.5, and qSOFA were risk factors for hospital mortality in patients with sepsis undergoing CRRT, but lactate level, mechanical ventilation support, PaO2/FiO2, platelet count, and indicators of acute kidney injury (AKI) like blood urea nitrogen (BUN) and creatinine were not independently associated with hospital mortality after adjusted by qSOFA. The risk nomograma and Kaplan–Meier curves verified that use of vasopressor and INR>1.5 possesses significant predictive value. Conclusions: Using Cox-LASSO regression model, use of vasopressor, INR>1.5 and qSOFA are found to be risk factors of hospital mortality in patients with Sepsis-3.0 received CRRT. This finding may assist clinicians in tailoring precise management and therapy for these patients undergoing CRRT.